Change of Adolescent Behavior by Information Technology in Pekuwon village Juwana District, Pati - Prasetyo, Joko; Atmaja, Hamdan Tri; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2019)
Modern information technology with various types and forms and facilities has been developed in many urban and rural areas. The tendency of adolescents to imitate the various information that can be obtained from technology. The purpose of this study is to describe: (1) utilization of information technology by youth Pekuwon village, Pati regency, (2) parental supervision on the use of information technology by adolescents in Pekuwon village, Pati Regency, (3) changes in adolescent behavior in connection with information technology in Pekuwon village. The location of this research is Pekuwon village Juwana sub-district. This research uses qualitative approach. The results of this study indicate that information technology in Pekuwon village trends are used for entertainment and support learning. There are 4 categories of families in providing youth supervision: (1) the family category that provides strict supervision, with an educated family background that cares for youth development, (2) the family categories that do not provide supervision (release) of adolescents with poor educated family background who are less concerned about adolescents, (3) the family category that provides supervision on certain things such as study time and prayer time, with educated family background that has been flexible in understanding the development of the times, (4) the family category that carries out supervision is an appeal, with the background as the village party who cares about adolescent development. Changes in adolescent behavior after the existence of information technology in Pekuwon village in the form of positive or negative behavior. The changes are categorized into 3 types, namely: shifts in cultural values, shifts in religious values, and asocial. This proves the truth of the theory of the arena-habitat of Piere Bourdieu.